Muscle non-invasive bladder cancer: clinical and morphological features, treatment outcomes, survival analysis - K. B. Lelyavin; V. V. Dvornichenko (Acta Biomedica Scientifica, 2013)
The article presents the analysis of the results of surgical treatment of 896 patients with muscle non-invasive bladder cancer who were operated in the period from 2000 to 2011: 662 (73,9 %) men and 234 (26,1 %) women of 31-84 years (average age - 61,6 years). The authors describe experience of using bipolar transurethral resection (TURis) and vaporization (vap) for a urinary bladder tumor. The article represents the study of frequency and nature of the recurrence and survival rate (common, oncology-specific, disease-free) after transurethral surgery of patients with non-muscle invasive bladder cancer (BC) of Ta, T1 and Tis stages. The obvious advantage of the technique bipolar transurethral resection (TURis) and vaporization (vap) over others suggests that in the nearest future the TURis-vap will serve as the "golden standard" in non-muscle invasive bladder tumors surgery.